If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4(x-2)=3x-6
We simplify the equation to the form, which is simple to understand
4(x-2)=3x-6
Reorder the terms in parentheses
+(+4x-8)=3x-6
Remove unnecessary parentheses
+4x-8=+3x-6
We move all terms containing x to the left and all other terms to the right.
+4x-3x=-6+8
We simplify left and right side of the equation.
+1x=+2
We divide both sides of the equation by 1 to get x.
x=2
| (18x+(2x^2)*y)dx-(x^2+4)dy=0 | | 6q^2-10q-4=0 | | 4/8=4/t | | n/4=25/5 | | 6q^2-11q-72=0 | | x/12=225/15 | | 12/16=x/24 | | 1.12= | | 12z^2+16z-28=0 | | (18+(2x^2)*y)dx-(x^2+4)dy=0 | | x/3=4-x | | 24n^2-40n+14=0 | | X^2+y^2+12x-8y+48=0 | | 15-5x-2-4= | | 2n-4=4+3n | | 112=x(x-5) | | 5a=12-a | | 6t(-3+t)=0 | | 1.6/0.25 | | 2+6=210 | | (5-3w+2u)(-8)= | | 9+3x=6+-2x | | 0.15x=3 | | 6/22=27/m | | 5b^2+52b+63=0 | | 6/16=m/56 | | 25r^2+80r+64= | | 2h^2+7h+6=0 | | 3.3(m+-6.4)=4.62 | | 9b^2+30bt+25t^2= | | w(w+4)+15=(w-3)(w+9) | | 5(x-1)=-45 |